THE ASSOCIATION BETWEEN FAMILY SUPPORT AND MENTAL HEALTH AMONG OUTPATIENTS WITH SCHIZOPHRENIA - Syafwa Aqilah; Rusni Masnina; Ni Wayan Wiwin Asthiningsih (LPPM STIKES HUSADA JOMBANG, 2026)
Background: Outpatients with schizophrenia still face the risk of mental health distress despite regular treatment. Family support is considered an important psychosocial factor that potentially plays a role in maintaining stable mental health. However, empirical evidence regarding the relationship between family support and mental health in patients with schizophrenia in primary healthcare settings is limited, particularly in the outpatient setting. Objectives: This study aims to analyze the relationship between family support and mental health in outpatients with schizophrenia. Methods: This study used a quantitative analytical design with a cross-sectional approach. The subjects were 40 outpatients with schizophrenia registered at the Loa Bakung Community Health Center, Samarinda, who were selected using total sampling. Family support was measured using the Duke–UNC Functional Social Support Questionnaire (FSSQ), while mental health was assessed using the General Health Questionnaire-12 (GHQ-12). Data were analyzed descriptively and bivariately using the Chi-square test with continuity correction, and presented with Odds Ratio (OR) values ​​and 95% confidence intervals with a significance level of p < 0.05. Results: The analysis results showed that the majority of respondents were in a state of mental health distress (72.5%). There was a statistically significant relationship between family support and the mental health of schizophrenia patients (p = 0.008). Respondents with adequate to high family support were less likely to experience mental health distress than respondents with low family support (OR = 0.061; 95% CI: 0.007–0.545). Conclusion: This study demonstrates a significant association between family support and mental health in outpatients with schizophrenia. However, given the cross-sectional design and limited sample size, these results cannot be used to conclude a causal relationship. These findings emphasize the importance of family support as a psychosocial factor that needs to be considered in community-based mental health services.